Teacher training for school inclusion in the modality of youth and adults education: analysis of research - Silva, Maria do Carmo Lobato da; Campos, Juliane Aparecida de Paula Perez (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2018)
This systematic review seeks to describe and analyze dissertations and theses that focus on initial and continuing teacher training for inclusion of students with disabilities in the EJA modality, from 2008 to 2016, available at the Digital Library of Theses and Dissertations (BDTD) and Bank of Dissertations and Thesis of Capes. The descriptors were teacher training, school inclusion, inclusive education, special education, disability, youth and adult education. Nine productions were selected for content analysis. The results pointed out three studies that focused the conception of teachers on their initial and continuous formation process, indicating them insufficient and fragile to work with students with disabilities in the EJA; four studies indicated that continuing education needs to occur in the daily life of the school to meet the needs of the teachers in service and two studies indicated the collaborative work as a strategy to improve teacher training. It was evidenced that the thematic teacher training for school inclusion in the EJA modality has been underprivileged in the productions that dialogue the interface between EJA and Special Education, making it opportune its debate for the advancement of knowledge and discussion on the (re) structuring of curriculums of graduation courses and reconfiguration of programs for continuing education.